Construção iterativa de uma ontologia com integração semântica para o observatório solar virtual do CRAAM - Santos, Israel Florentino dos (2017)
The signi cant increase of data requires a new research model, which must integrate theory, experimentation and simulation. This new paradigm, called e-Science, considers that the evolution of science depends on the union of scientists from di erent areas with professionals from Information Technology. Consistent with this new view of science, the present study aims to construct a semantic layer that allows an elaborated ontology to enable the coupling of programming language, web service, and inference. The Virtual Solar Observatory of the Center for Radio Astronomy and Astrophysics Mackenzie, responsible for the collection and management of data, with a view to promoting its integration with the other members of the International Virtual Observatory Alliance (IVOA). To support the semantic construction, a framework was used that integrated the JAVA and Python languages to process and analyze the data allowing full integration between the various observatories. The need of the present study was necessary due to the de ciencies in many ontologies with regard to expansion and integration. This study was based on Computational Ontology, Semantic Web and the characteristics of the e-Science paradigm. For an ontology construction, a methodology was used for the characterization of the Methontology and Enterprise, predicting iterative constructions and continuous revisions and documentation during the process. The results showed that, through the construction of the SST module in the Python programming language and the elaboration of a database view in RDF, it was possible to favor the integration of the elaborated ontology for other members of the IVOA. Thus, this study aims to provide scientists, students and researchers in the eld of Astronomy a reliable environment for the sharing of solar data.